Influence of Family Benefits on Women’s Professional Activity. The cases of Poland, the United Kingdom, and France - Kacperska, Magdalena (Studia Historiae Oeconomicae, 2019)
Women show greater and greater activity on the job market, they obtain better positions, salaries, etc. However, the statistics concerning their professional activity differ from those of men. We should take into consideration the fact that women are the ones who give birth to children and, in majority, take care of their upbringing, especially in the first years of child’s life. Policies of particular states are different in terms of the amount and availability of family benefits, and that can be reflected in women’s willingness to return to work.